Research on Chlamydia trachomatis in women from the municipal district of Piraí-Rio de Janeiro - Varella, Renata de Q.; Passos, Mauro R.L.; Pinheiro, Vandira M.S.; Lopes, Helena R.; Santos, Sérgio B.; Guimarães, Cristiane C.; Angelis, Flávia de (Brazilian Journal of Sexually Transmitted Diseases, 2000)
The Chlamydia tachomatis is an importam agem causer of endocervicitis in sexually active women. lt can be asympromaric or presem unspccific symproms. Uorreatcd and nor diagnosed infection represems a serious problem on public healrh since there is a grear risk for developing endomerriris, pelvic inflamatory diseasc (PID) wirh rhe resulrant sequelar of infcrtiliry and neonatal infecrions (pneumonitis and conjumivitis). Althrough rhere is a very low number of prevalence among brazilian women. Goals: Determine rhe frcqucncy of endocervicitis by C. Trachomatis among women who arrend public and private clinics in Pirar - RJ. Methods: A prospecrive srudy was done among sexually active women 13 ro 49 years of age who looked for a gynccologist for severa! different reasons and hadn't used any kind of vaginal medicine during rhe preceding 2 weeks. The srudy involvcd anamnese, gynecologic exam for oncoric ciroparology and endocervical collect wirh specific swab. The endoccrvical samples were submined to Elisa through Elia-Vidas sysrem for detecring Chlamydial anrigen ar rhe STD Labocatory of the Universidade Federal Fluminense (UFF), Niterói - RJ. Resulrs: The srudy was composed by 108 paticnrs (69 from public service and 39 from privare clinics). Chlamydia antigens were derccted in 20 women, 18,8% (13/69) from public service and 18% (7/39) from private clinics, who wem to rhc docror for diffcrcm maio reasoos such as routine and vaginal dischargc and/or pelvic pain. Conclusions: The total rate of Chlamydia positive results was 18,5% (20/108) and there was no significam different berween prevalences in public and private service. Clinic and citopatologic exams are oor enough 10 sustain Chlamydia infections diagnosis.